3 2 8 8 × 3 4 3 2 × 3 6 4 8 = ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Wonderful factorization of numbers. Bonus question: Without using a calculator, evaluate the expression below.
( 3 2 8 8 + 3 4 3 2 + 3 6 4 8 ) × [ ( 3 2 8 8 − 3 4 3 2 ) 2 + ( 3 4 3 2 − 3 6 4 8 ) 2 + ( 3 6 4 8 − 3 2 8 8 ) 2 ]
[Response to Challenge Master Note]
Let a = 3 2 8 8 , b = 3 4 3 2 and c = 3 6 4 8 . The given expression (call it E ) to be evaluated is,
E = ( a + b + c ) [ ( a − b ) 2 + ( b − c ) 2 + ( c − a ) 2 ] = 2 ( a + b + c ) ( a 2 + b 2 + c 2 − a b − b c − c a ) = 2 ( a 3 + b 3 + c 3 − 3 a b c ) = 2 ( 2 8 8 + 4 3 2 + 6 4 8 − 3 × 4 3 2 ) = 1 4 4
Response to Nihar Mahajan: Check this one. The equation is in form of X.3X/2.9X/4 whole cube rooted. Now simple multiplication gives us 27.X^3/8 cube rooted. removing cube root. gives us 3X/2. which is the middle number 432
We know that,
3 a ∗ 3 b ∗ 3 c = 3 a b c
Now, Note that:-
2 8 8 = 2 ∗ 1 2 ∗ 1 2
4 3 2 = 6 ∗ 6 ∗ 1 2
6 4 8 = 2 ∗ 2 ∗ 6 ∗ 2 7
Therefore,
3 2 8 8 ∗ 4 3 2 ∗ 6 4 8 = 3 2 ∗ 2 ∗ 2 ∗ 1 2 ∗ 1 2 ∗ 1 2 ∗ 6 ∗ 6 ∗ 6 ∗ 3 ∗ 3 ∗ 3
3 2 3 ∗ 3 3 ∗ 6 3 ∗ 1 2 3 = ( 3 4 3 2 3 = 4 3 2
Hence, The answer is 4 3 2
Nice way to factorizing the terms "half way". Good work! Bonus question: Because it's only true that A × B = A B when A , B ≥ 0 ; is it also true that 3 A × 3 B = 3 A B only when A , B ≥ 0 ?
3 2 8 8 × 3 4 3 2 × 3 6 4 8 = 3 2 8 8 × 4 3 2 × 6 4 8 = 3 1 4 4 × 2 × 4 3 2 × 2 1 6 × 3 = 3 1 4 4 × 3 × 4 3 2 × 2 1 6 × 2 = 3 4 3 2 × 4 3 2 × 4 3 2 = 3 ( 4 3 2 ) 3 = 4 3 2
I wasn't expecting this. Nicely done!
Problem Loading...
Note Loading...
Set Loading...
3 2 8 8 × 3 4 3 2 × 3 6 4 8 = 3 2 5 3 2 × 3 2 4 3 3 × 3 2 3 3 4 = 3 2 1 2 3 9 = 2 4 3 3 = 4 3 2